Government Legal Action In The Protection Of Indonesian Workers Victims Of Trafficking Crimes - Nabila Qurotuaini; Aliza Amalina Mukaromah; Radityo Dwi Prasojo; Rahmah Aliyah (Faculty of Law, Muhammadiyah University of Surabaya, 2023)
Legal action by the Indonesian government to protect trafficked workers. Through law enforcement, prevention, education, rehabilitation, and international cooperation, governments are committed to protecting the rights and well-being of victims. Several laws, such as the Indonesian Labor Protection Law and the Law on Combating Trafficking in Persons, provided the primary legal basis for victim protection. These protective measures include prevention, law enforcement, and rehabilitation in accordance with human rights principles. However, challenges remained in protecting the workforce, especially those vulnerable to trafficking. Further efforts are needed to enforce the law, improve regulations, and raise public awareness to address the trafficking problem that impacts the lives of Indonesian workers. Keywords: human traficking, rehabilitation, crime